Pengaruh Pertumbuhan Ekonomi dan Produktivitas Tenaga Kera Serta Tingkat Pendidikan Terhadap Tingkat Kemiskinan Di Provinsi Kalimantan Timur (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The effect of economic growth and labor productivity and education levels of the level of poverty in the province of East Kalimantan 2006-2015. The purpose of this study was to determine the effect of economic growth, labor productivity and education levels of the level of poverty. The theory used in this research is a theoretical concept kemisikanan which is influenced by the number of population, labor force education levels. This study uses data obtained from the Central Statistics Agency (BPS). The analytical method used in this research is multiple linear regression analysis. From the analysis of the data that I do can be concluded that (1) Growth significant effect with directions negatively related to the level of poverty in the province of East Kalimantan (2) Productivity Labor significant effect with directions negatively related to the level of poverty in the province of East Kalimantan (3) Education level not significant positive correlation with the direction of the level of poverty in the province of East Kalimantan year.Keywords: Economic Groeth, Labor Productivity, Education